Portaria CMPF nº 41, de 4 de julho de 2019 - Oswaldo Jose Barbosa Silva (DOU, Brasília, DF, 9 jul. 2019. Seção 2, p. 58., 2019)
Dispensa do encargo de Corregedor Auxiliar da Corregedoria do Ministério Público Federal.